2016
DOI: 10.4236/jbm.2016.411006
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of the Methanolic Extract of Lemongrass and Some Antibiotics to Treat Urinary Tract Bacteria

Abstract: Some medicinal plants are used traditionally in Saudi Arabia to treat many bacterial infections. Three plants, lemongrass (Oymbopogon citrates), lantana (Lantana camara), and wild olive leaves (Olea europaea) were collected, identified, extracted with either hot water or organic solvents (methanol, diethyl ether, ethyl acetate and n-butanol) to investigate their antibacterial activities against E. coli. The methanol extracts of lemongrass, lantana and olive showed the highest activities against Esherichia coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The FICI is based on the Loewe additivity zero interaction theory [ 7 – 9 ]. A FICI of ≤ 0.5 indicates synergism, > 0.5 to 1 indicates additive effects, > 1 to ≤ 4 indifference, and > 4 is considered to be antagonism [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FICI is based on the Loewe additivity zero interaction theory [ 7 – 9 ]. A FICI of ≤ 0.5 indicates synergism, > 0.5 to 1 indicates additive effects, > 1 to ≤ 4 indifference, and > 4 is considered to be antagonism [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Vural et al [115] found that the essential oil extracted from olive leaves displayed a highly intriguing volatile composition, showcasing potent antibacterial activity [115]. Vegetal extract Ø = 13-18.5 mg/mL MIC = 12.5-25 mg/mL MBC = 25-50 mg/mL [102,105] Leaves Essential oil Ø = 9-29 mm MIC = 0.625-5 mg/mL [6,96,115,117] Vegetal extract Ø = 1-20 mm MIC = 0.60-25 mg/mL MBC = 0.70-12.5 mg/mL [109,110,[118][119][120][121][122][123][124][125][126][127] Ø = zone of inhibition; MIC = minimum inhibition concentration; MBC = minimum bactericidal concentration; GN = Gram negative; GP = Gram positive.…”
Section: Antibacterial Activitymentioning
confidence: 99%